The Effectiveness of Ballon Blowing Exercise on Increasing Expiratory Forced Volume Value in 1 Second (FEV1) and Oxygen Saturation among COPD patients - Moch Dadang Suharno; I Ketut Sudiana; Ninuk Dian K; Abu Bakar; Muhammad Amin; Tintin Sukartini; Argo Winoto (Alta Dharma Publisher, 2020)
Balloon-blowing exercise is a breathing technique that is used to reduce breathlessness and improve lung expansion. The purpose of this study is to explain the difference in effectiveness balloon blowing exercise to the increase in value FEV1 and oxygen saturation in COPD patients. This study used a quasi-experimental design with a pre-test post-test study; the study population was patients with COPD in Taman Husada Bontang hospitals. Consecutive sampling techniques do sampling following the inclusion criteria, with a total of 20 patients. Intervention balloon blowing exercise performed 3 times per week within 4 weeks. The results showed that there are positive effects on FEV1 (p-value= 0.001) and oxygen saturation (p-value 0.02). Balloon-blowing exercise could increase in value FEV1 and oxygen saturation in patients with COPD